Patient education among nurses: bringing evidence into clinical applicability in Iran - Karimi Moonaghi, Hossein; Emami Zeydi, Amir; Mirhaghi, Amir (Investigación y Educación en Enfermería, 2016)
Objective. The aim of this study was to present a comprehensive review of the literatures describing barriers and facilitators of patient education (PE) perceived by Iranian nurses in order to explain clinical applicability of patient education. Methods. Review of the literature was undertaken using the international databases including PubMed/Medline, Scopus, ScienceDirect, as well as Google Scholar. Also, Persian electronic databases such as Magiran, SID and IranMedex were searched. Electronic databases were searched up from conception to September 2014 using search terms: "patient education", " patients education", "patient teaching", "patient training", "nurse", " nurses", " nursing", " and "Iran". Only studies were included that were related to barriers and facilitators of PE among Iranian nurses. Results. Twenty-seven studies were included. The main influential barriers were categorized into three major areas: 1) Nurse-related factors: nursing shortage 2) Administration-related factors: unsupportive organizational culture, and 3) Patient-related factors: low compliance. The most perceived facilitators were recognized as “increasing, selecting and training special nurses for providing PE” and “providing PE courses for nurses and appropriate facilities for PE”. Conclusion. Iranian nurses encounter barriers in PE, and the most frequently encountered barriers were related to administration factors. These findings have implications for administrators and managers in health settings. In order to promote PE among nurses, administrators should create a supportive environment and use effective strategies to smooth the progress of PE by nurses in their practice in order to ensure optimal outcomes for patients. How to cite this article: Karimi Moonaghi H, Emami-Zeydi A, Mirhaghi A. Patient education among nurses: Bringing evidence into clinical applicability in Iran. Invest Educ Enferm. 2016; 34(1): 137-151